The use of Moringa oleifera in ruminant feeding and its contribution to climate change mitigation - Amad, Abdulkarim Abdulmageed; Zentek, Jürgen (Frontiers in Animal Science, 2023)
Livestock production in developing countries faces several difficulties such as a general shortage of feed resources, their regional availability and quality. The climate change will further exacerbate these problems and might lead to a massive reduction in ruminants’ productivity. Therefore, there is a need for the use of adaptable and resilient forage plants that can also contribute to reducing greenhouse gases at the same time. The Moringa oleifera tree is well known as agroforestry tree and adapted to growing in harsh conditions, it produces a high biomass in a short period and it contains high levels of nutrients and biologically active components. All parts of the Moringa tree are valuable and thus have multiple benefits and applications. So, Moringa oleifera has great potential and can be used as a forage crop, storing carbon dioxide (CO2) with improving ruminant’s performance and the livelihoods of farmers in the tropics. This paper aimed to present the results and findings of studies related to the use of Moringa in ruminants feed (cattle, sheep and goat) and its contribution to climate protection. Several researches highlighted that M. oleifera can be used as green fodder individually or in combination with other crops and concentrate feeds for ruminants to improve the performance such as growth rate, milk yield and milk constituents without negative impact on animal health. This improvement in performance could be attributed to the favorable nutrient content in M. oleifera, especially delivering protein in conjunction with its bioactive compounds such as alkaloids, flavonoids, phenolics, glucosinolates, carotenoids, sterols, saponins, phenolic acids, tannins and isothiocyanates. Furthermore, it has been shown that this plant produces high yields and so it might be an excellent carbon dioxide sink absorbing and utilizing carbon dioxide, thus reducing the anthropogenic load of carbon dioxide in the atmosphere. In addition, feeding cattle and other ruminants with M. oleifera leaves or seeds decreases the ruminal methane emissions significantly which could contribute additionally to adapting to climate friendly farming. Thus, the use of Moringa can make a sustainable contribution to strengthening animal production, especially in countries with limited feed resources.